Efficacy of Profilactic and Therapeutic Antibiotic in Congenital Hydrocephalus Shunt Infection - Akhmad Imron; Kahdar Wiriadisastra (Journal of Medicine and Health, 2015)
Prophylactic dose antibiotic are indicated in patients having neurosurgical clean operations with implant surgery. The aim of this study is to evaluate the efficacy of prophylactic dose antibiotic in shunt infection. Between 1 October 2009 until 31 September 2011, 102 patients with congenital hydrocephalus who underwent VP shunt surgery. Fifty-one received profilactic antibiotic (ceftriaxone 50-75 mg/kgBW), 30-60 minutes before surgery until 5 days post-operative, and 51 patients received therapeutic antibiotic  (ceftriaxone 50-75 mg/kgBW), 30-60 minutes before surgery until 1 days post-operative. All patient were followed for 1-6 months to evaluate shunt infection. Collected data will be statistically analyzed. The study found that the rate of infection is 17,6% (9 patients of 51 patients) who received therapeutic antibiotic, and 17,6% (9 patients of 51 patients) who received profilactic antibiotic.There is not statistically significant between all group in shunt infection (p=1,000). Others risk factors significantly influence shunt infection are enlargement of the head (p=0,002), length of surgery (p=0,00327), time of surgery (p=0,00077) and nutrition status (p=0,01343). The results of this study indicate that profilactic antibiotic effective to prevent shunt infection in congenital hydrocephalus. Others risk factors significantly influence are enlargement of the head, length of surgery, time of surgery and nutrition status. Keywords:  antibiotic,  prophylactic, infection, VP shunt, congenital hydrocephalus